Santonian (Late Cretaceous) echinoids from the Santander area (northern Cantabria, Spain) - Schlüter, Nils; Wiese, Frank; Díaz-Isa, Manuel; Püttmann, Tobias; Walaszczyk, Ireneus (Cretaceous research, 2023)
Eight echinoid species are described from Upper Cretaceous marl-limestone alternations from a temporary outcrop in the neighbourhood of the village of Mompia (northern Cantabria, Spain): Temnocidaris (Stereocidaris) mengaudi, Pseudoholaster pachecoi, Roweaster cantaber, Micraster turonensis, Micraster mengaudi, Bolbaster micranthus and two newly described species: the phymosomatoid Cosmocyphus cantaber sp. nov. and the micrasterid Micraster quebrada sp. nov. The three Micraster species reveal an astonishing and extreme degree of intraspecific variation, in particular the degree of inflation of the test. This has not yet been detected in any other spatangoid species before. The majority of reported echinoids are restricted to the working area, and hence are likely endemic to this area. An integrated stratigraphic approach using ammonites, inoceramid bivalves, calcareous nannofossils and stable carbon isotopes localises the echinoid assemblage in the upper middle and lower upper Santonian.
Online verfügbar 24. Januar 2023, Artikelversion 21. März 2023
Gesehen am 19.05.2023